Conformation of yeast 18S rRNA. Direct chemical probing of the 5' domain in ribosomal subunits and in deproteinized RNA by reverse transcriptase mapping of dimethyl sulfate-accessible. - Lempereur, L (1985)
The structure of the 5' domain of yeast 18S rRNA has been probed by dimethyl sulfate (DMS), either in "native" deproteinized molecules or in the 40S ribosomal subunits. DMS-reacted RNA has been used as a template for reverse transcription and a large number of reactive sites, corresponding to all types of bases have been mapped by a primer extension procedure, taking advantage of blocks in cDNA elongation immediately upstream from bases methylated at atom positions involved in the base-pair recognition of the template. Since the same atom positions are protected from DMS in base-paired nucleotides, the secondary structure status of each nucleotide can be directly assessed in this procedure, thus allowing to evaluate the potential contribution of proteins in modulating subunit rRNA conformation. While the DMS probing of deproteinized rRNA confirms a number of helical stems predicted by phylogenetic comparisons, it is remarkable that a few additional base-pairings, while proven by the comparative analysis, appear to require the presence of the bound ribosomal subunit proteins to be stabilized.